2008
DOI: 10.1143/jjap.47.2945
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Electro-Optic Modulator Fabricated on Silicon Substrate Utilizing the Three-Terminal Transistor Waveguide Structure

Abstract: J a g &%B %B* ( R e c e i v e d 19 June 1 9 8 6 ) I t i s assumed i n t h i s paper that the interquark (or gtuon) forces are dominated by color octet exchange, which leads t o the attractive forces t o form colored bound states. states i s discussed i n two quasi-confinement modeZs. diction of the espe2rimentaZ signature on the colored bound states 5s included. I t i s w i d e l y b e l i e v e d t h a t w i t h i n t h e framework o f QCD c o l o r i s conf i n e d , however, t h i s r e m a i n s t o be c o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The relevant process involved in fabricating the aforementioned silicon light intensity modulators has already been reported elsewhere [9]. A brief detail on the realization of optical modulators is provided as follows.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The relevant process involved in fabricating the aforementioned silicon light intensity modulators has already been reported elsewhere [9]. A brief detail on the realization of optical modulators is provided as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the subtleties of various processes involved in the fabrication and characterization of modulators, we believe that there are still quite a few delicate issues that deserve to be fully explored in greater detail. For example, our previous result [9] had demonstrated that only short modulation devices clearly exhibited their sensitivity in their modulation lengths. In addition, the magnitude of biasing gate current had a relative minor effect on the modulation depth measured.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Since the modulation of silicon is predominantly and most efficiently achieved by carrier injection or plasma dispersion, 3) both p-i-n diode 4,5) and transistor, [6][7][8][9] therefore, are two of most frequently adopted electrical device structures for the various designs of silicon modulators. Previously, we had managed to fabricate junction field-effect transistor (JFET)-based silicon waveguide modulators with modulation depth close to 100% at V DS ¼ AE5 V when 5 mA gate current was administered.…”
Section: Introductionmentioning
confidence: 99%